2014
DOI: 10.1186/1471-2431-14-182
|View full text |Cite
|
Sign up to set email alerts
|

Parent and family impact of raising a child with perinatal stroke

Abstract: BackgroundPerinatal stroke is a leading cause of early brain injury, cerebral palsy, and lifelong neurological morbidity. No study to date has examined the impact of raising a child with perinatal stroke on parents and families. However, a large breadth of research suggests that parents, especially mothers, may be at increased risk for psychological concerns. The primary aim of this study was to examine the impact of raising a child with perinatal stroke on mothers’ wellbeing. A secondary aim was to examine ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 47 publications
3
36
1
6
Order By: Relevance
“…It was suggested that these findings might be due to the primary role of mothers in child care. On the other hand, Bemister et al demonstrated that mothers had slightly higher depression levels than fathers in the study performed in USA (13). In contrast to these findings, Al-Gamal et al reported no difference on depression levels of mothers and fathers of children with CP (14).…”
Section: Discussioncontrasting
confidence: 40%
“…It was suggested that these findings might be due to the primary role of mothers in child care. On the other hand, Bemister et al demonstrated that mothers had slightly higher depression levels than fathers in the study performed in USA (13). In contrast to these findings, Al-Gamal et al reported no difference on depression levels of mothers and fathers of children with CP (14).…”
Section: Discussioncontrasting
confidence: 40%
“…Parents mentioned the strong sense of guilt and self-blame experienced after a diagnosis of perinatal stroke – a recognised problem [74, 75]:… you blame yourself and then you, you think that everyone else is blaming you as well. – Mother, Focus group 1…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, following a diagnosis of perinatal stroke, families experience a range of emotions including feelings of guilt and self-blame [74, 75]. There is also uncertainty about the future in terms of the nature and severity of difficulties their child may face.…”
Section: Discussionmentioning
confidence: 99%
“…230 Severity of disability after perinatal stroke correlates with maternal psychosocial outcomes such as depression and quality of life. 231 …”
mentioning
confidence: 99%